Study on the Ash Deposition Characteristics for Co-Combustion of Zhundong Coal with Cotton Stalk - Tianyou Li; Ning Liu; Kunpeng Liu; Bo Wei; Jianjiang Wang; Feng Wang; Yanjie Qi; Ning Chen (Applied Sciences, 2025)
With the rapid development of renewable energy, the co-combustion of Zhundong coal and biomass has attracted more and more attention. However, the high content of alkali metals in Zhundong coal and biomass leads to serious slagging and fouling in the co-combustion process. In this study, cotton straw was selected for co-combustion with Zhundong coal. The ash deposition model was established according to the melting ration calculated by Factsage, and the ash deposition characteristics during the co-combustion of Zhundong coal and cotton stalks in the actual boiler were explored by Fluent. The results showed that the K2O content in ash increased from 0.31% to 9.31% with the increase in the blending ratio, while the contents of other components had no significant changes. In addition, with the increase in the blending ratio, the ash deposition rate increased from 0.00327 kg/(m2·s) to 0.00581 kg/(m2·s), an increase of 77.6%. The reduction in the tangential circle diameter obviously alleviated the ash deposition on the wall. When the tangential circle diameter was reduced to 400 mm, the ash deposition rate was 0.00207 kg/(m2·s), which was 37.6% lower than the original condition.